2022
DOI: 10.3390/microorganisms10010143
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Evolution and Spike-Specific CD4+ T-Cell Response in Persistent COVID-19 with Severe HIV Immune Suppression

Abstract: Intra-host evolution of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has been reported in cases with persistent coronavirus disease 2019 (COVID-19). In this study, we describe a severely immunosuppressed individual with HIV-1/SARS-CoV-2 coinfection with a long-term course of SARS-CoV-2 infection. A 28-year-old man was diagnosed with HIV-1 infection (CD4+ count: 3 cells/µL nd 563000 HIV-1 RNA copies/mL) and simultaneous Pneumocystis jirovecii pneumonia, disseminated Mycobacterium avium complex i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 48 publications
(58 reference statements)
2
8
0
Order By: Relevance
“…These mutations appeared to be adaptive at the within-host level due to their concentration in the spike protein, with several common to other variants of concern. Similar results have been observed in other patients with long-term infections of SARS-CoV-2 [21,22], including those who have been treated with convalescent plasma, indicating antigenic evolution within the host [23] (although some immunocompromised individuals show little to no within-host evolution of SARS-CoV-2 [24]). A study of infection in immunocompromised individuals has found that mutations accumulate in the spike gene receptor binding domain and N-terminal domains, associated with immune escape and viral packaging [25].…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…These mutations appeared to be adaptive at the within-host level due to their concentration in the spike protein, with several common to other variants of concern. Similar results have been observed in other patients with long-term infections of SARS-CoV-2 [21,22], including those who have been treated with convalescent plasma, indicating antigenic evolution within the host [23] (although some immunocompromised individuals show little to no within-host evolution of SARS-CoV-2 [24]). A study of infection in immunocompromised individuals has found that mutations accumulate in the spike gene receptor binding domain and N-terminal domains, associated with immune escape and viral packaging [25].…”
Section: Introductionsupporting
confidence: 82%
“…Specialisation on immunocompromised individuals has been observed for other pathogens (e.g. Pseudomonas aeruginosa infections in cystic fibrosis patients [47]) and longitudinal studies of prolonged SARS-CoV-2 infections reveal the rapid accumulation of many mutations [2024], but it is unclear if and when this leads to specialisation with a reduction in fitness on immunocompetent hosts.…”
Section: Discussionmentioning
confidence: 99%
“…These mutations appeared to be adaptive at the within-host level due to their concentration in the spike protein, with several common to other variants of concern. Similar results have been observed in other patients with long-term infections of SARS-CoV-2 [ 21 , 22 ], including those who have been treated with convalescent plasma, indicating antigenic evolution within the host [ 23 ] (although some immunocompromised individuals show little to no within-host evolution of SARS-CoV-2 [ 24 ]). A study of infection in immunocompromised individuals has found that mutations accumulate in the spike gene receptor binding domain and N-terminal domains, associated with immune escape and viral packaging [ 25 ].…”
Section: Introductionsupporting
confidence: 82%
“…According to them, ‘the virus could (1) have circulated and evolved in a population with little surveillance and sequencing; (2) it could have originated in an immuno‐compromised COVID‐19 patient or (3) it might have evolved in a nonhuman species, from which it recently followed a trajectory of secondary colonization in people’ (hereafter H1, H2 and H3). The second option appears to be the hypothesis of choice for many, especially associated with patients with human immunodeficiency virus (Healy, 2021a , 2021b ) despite recent opposing evidence (Álvarez et al., 2022 ). Empirical and theoretical analyses presented herein are also not in accordance with the origin of Omicron in immunodeficient humans (H1) nor in isolated human populations (H2).…”
Section: Revelations From Omicronmentioning
confidence: 99%